Seroprevalence of Newcastle Disease (ND) Virus and Detection of Antigen on Domestic Chicken in District Lembar, West Lombok - Y., Hamdani; Kencana, G. A. Y. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
This study to determine seroprevalence of newcastle disease (ND) virus and detection of antigen on domestic chicken in district lembar, west lombok regency. A total of 6 (six) villages, serve as research sites namely Labuan Tereng Village, Lembar Selatan Village, Lembar Village, Jembatan Kembar Village, East Jembatan Kembar Village, and Nyiur Lembang Village. The samples were sera cloaca swab and tracheal swab taken by simple random sampling. A total of 150 poultry chickens each were taken sera, cloaca swab, and tracheal swab so that the number of samples to 150 sera samples, 150 samples of cloaca swabs, and 150 tracheal samples. Sera was examined by serological test of haemagglutination inhibition (HI) test while antigen detection was performed by hemagglutination (HA) test followed by Reverse Transcriptase Polymrase Chain Reaction (RT-PCR) test. Serology test results from 150 sera samples showed as many as 50 sera samples (33%) positive ND with titer of 22-29 HI units. While the antigen test results from 15 pooled samples showed as many as four positive samples of HA test and RT-PCR test showed a positive four samples with 380bp base length. It is concluded that ND virus infections have occurred in dstrict Lembar, West Lombok regency which hasbeen officially not yet reported. Keywords: Seroprevalence, antigen detection, Newcastle Disease, domestic chicken, West Lombok.